Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Claro, vamos a analizar y resolver la función [tex]\( F(x) = 2x^3 - 3x^2 + 7 \)[/tex] para los valores dados de [tex]\( x \)[/tex].
Primero, evaluamos [tex]\( F(-1) \)[/tex]:
[tex]\[ F(-1) = 2(-1)^3 - 3(-1)^2 + 7 \][/tex]
El cálculo paso a paso sería:
[tex]\[ (-1)^3 = -1 \][/tex]
[tex]\[ 2(-1) = -2 \][/tex]
[tex]\[ (-1)^2 = 1 \][/tex]
[tex]\[ 3(1) = 3 \][/tex]
Entonces:
[tex]\[ F(-1) = -2 - 3 + 7 \][/tex]
[tex]\[ F(-1) = 2 \][/tex]
Ahora, evaluamos [tex]\( F(1) \)[/tex]:
[tex]\[ F(1) = 2(1)^3 - 3(1)^2 + 7 \][/tex]
El cálculo paso a paso sería:
[tex]\[ (1)^3 = 1 \][/tex]
[tex]\[ 2(1) = 2 \][/tex]
[tex]\[ (1)^2 = 1, 3(1) = 3 \][/tex]
Entonces:
[tex]\[ F(1) = 2 - 3 + 7 \][/tex]
[tex]\[ F(1) = 6 \][/tex]
Finalmente, evaluamos [tex]\( F(2) \)[/tex]:
[tex]\[ F(2) = 2(2)^3 - 3(2)^2 + 7 \][/tex]
El cálculo paso a paso sería:
[tex]\[ (2)^3 = 8 \][/tex]
[tex]\[ 2(8) = 16 \][/tex]
[tex]\[ (2)^2 = 4 \][/tex]
[tex]\[ 3(4) = 12 \][/tex]
Entonces:
[tex]\[ F(2) = 16 - 12 + 7 \][/tex]
[tex]\[ F(2) = 11 \][/tex]
Con estos resultados, completamos el cuadro:
[tex]\[ \begin{array}{l} F(-1) = 2 \\ F(1) = 6 \\ F(2) = 11 \\ 2 \\ 6 \\ 8 \\ \end{array} \][/tex]
Los resultados correctos de [tex]\( F(x) \)[/tex] son:
[tex]\[ F(-1) = 2, F(1) = 6, F(2) = 11 \][/tex]
Primero, evaluamos [tex]\( F(-1) \)[/tex]:
[tex]\[ F(-1) = 2(-1)^3 - 3(-1)^2 + 7 \][/tex]
El cálculo paso a paso sería:
[tex]\[ (-1)^3 = -1 \][/tex]
[tex]\[ 2(-1) = -2 \][/tex]
[tex]\[ (-1)^2 = 1 \][/tex]
[tex]\[ 3(1) = 3 \][/tex]
Entonces:
[tex]\[ F(-1) = -2 - 3 + 7 \][/tex]
[tex]\[ F(-1) = 2 \][/tex]
Ahora, evaluamos [tex]\( F(1) \)[/tex]:
[tex]\[ F(1) = 2(1)^3 - 3(1)^2 + 7 \][/tex]
El cálculo paso a paso sería:
[tex]\[ (1)^3 = 1 \][/tex]
[tex]\[ 2(1) = 2 \][/tex]
[tex]\[ (1)^2 = 1, 3(1) = 3 \][/tex]
Entonces:
[tex]\[ F(1) = 2 - 3 + 7 \][/tex]
[tex]\[ F(1) = 6 \][/tex]
Finalmente, evaluamos [tex]\( F(2) \)[/tex]:
[tex]\[ F(2) = 2(2)^3 - 3(2)^2 + 7 \][/tex]
El cálculo paso a paso sería:
[tex]\[ (2)^3 = 8 \][/tex]
[tex]\[ 2(8) = 16 \][/tex]
[tex]\[ (2)^2 = 4 \][/tex]
[tex]\[ 3(4) = 12 \][/tex]
Entonces:
[tex]\[ F(2) = 16 - 12 + 7 \][/tex]
[tex]\[ F(2) = 11 \][/tex]
Con estos resultados, completamos el cuadro:
[tex]\[ \begin{array}{l} F(-1) = 2 \\ F(1) = 6 \\ F(2) = 11 \\ 2 \\ 6 \\ 8 \\ \end{array} \][/tex]
Los resultados correctos de [tex]\( F(x) \)[/tex] son:
[tex]\[ F(-1) = 2, F(1) = 6, F(2) = 11 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.